Dynamic Estimation of Non Invasive Intracranial Pressure Using Svm with External Recurrences - Chacon-Pacheco, M (Springer Verlag, 2015)
Intracranial Pressure measurements are of great importance for the diagnosis, monitoring and treatment of many vascular brain disturbances. The standard measurement of Intracranial Pressure is performed invasively by perforation of the cranial scalp in the presence of a severe injury. Measuring Intracranial Pressure in a noninvasive way is relevant for a large number of pathologies where the invasive procedure represents a high risk. The method proposed in this study uses the Arterial Blood Pressure and the Cerebral Blood Flow Velocity –which may be obtained by noninvasive methods– to continuously estimate Intracranial Pressure. The results show that it is possible to estimate Intracranial Pressure using a non-linear Support Vector Machine with a correlation coefficient of 0.74 and a maximum deviation below 2 mmHg, which is comparable with (invasive) direct measurement instruments. © Springer International Publishing Switzerland 2015.